Círculos dialógicos em contexto educacional militar: políticas curriculares e suas articulações com a língua inglesa no ensino médio - Cardoso, Silvia Silveira (2018)
The present work has as central theme the relationship between curricular policies and the English language (LI) in high school. The main objective of this research is to understand the production of meanings in the relation between curricular policies and the English language, considering the implications for educational processes in high school. The educational institution where the research was carried out is a federal school located in the Western region of the city of Santa Maria, RS. The methodology used to develop this study contemplates a qualitative research-action approach. As a data source, investigative-formative dialogues were conducted with English-speaking teachers who develop pedagogical actions in high school. In order to base this research, the studies of the following authors were used as theoretical reference: Bardin (2011), Kuenzer (2013), Leffa (1999), Lopes e Macedo (2002), Minayo (2007), Saviani (2007). It has been found that investigating and discussing the English curriculum policies is fundamental, since it is perceived that teaching-learning has proved to be fragile, not reflecting meaningful learning from the students. From the dialogical practices, the educators evidenced the innumerable gaps and contradictions permeated by political questions that end up in the emptying of the social function of the LI as discipline in the school curriculum. Thus, as a product of this research, a group of studies was created in the Military School with the title of "Investigative-Formative Dialogical Circles at Wagon College", so that we could continue the dialogic and reflexive practices within the school environment.